THE FAUNA OF GASTROINTESTINAL TRACT’S NEMATODES OF SMALL CATTLE AT THE TERRITORY OF THE CHECHEN REPUBLIC - R. H. Gayrabekov; L. A. Altamirova; M. M. Salmanova; A. K. Sharipova (Юг России: экология, развитие, 2014)
Sheeping is the oldest and most important part of the agriculture of the Chechen Republic. It’s necessary to pay great attention to diseases and especially helminthes to solve the problems of sheep development along with the actions for forage reserving and sheep breeding. The helminthoses are wide spread among agricultural animals. They cause productivity decrease and in some cases even fatal death of animals.